Fibrin Sealant and Lipoabdominoplasty in Obese Grade 1 and 2 Patients - Mabrouk, Amr Abdel Wahab; Helal, Hesham Aly; Al Mekkawy, Soha Fathy; Mahmoud, Nada Abdel Sattar; Abdel-Salam, Ahmed Mohamed (Archives of Plastic Surgery, 2013)
Background Ever since lipoabdominoplasty was first developed to achieve better aesthetic outcomes and less morbidity, the rate of seroma formation, especially in obese patients, has disturbed plastic surgeons. The aim of this study was to evaluate the effect of fibrin sealant in the prevention of seroma formation after lipoabdominoplasty in obese patients.Methods Sixty patients with a body mass index (BMI) between 30 and 39.9 were assigned randomly to 1 of 2 groups (30 patients each). Group A underwent lipoabdominoplasty with fibrin glue, while group B underwent traditional lipoabdominoplasty; both had closed suction drainage applied to the abdomen. The patients' demographics and postoperative complications were recorded. Seroma was detected using abdominal ultrasound examinations at two postoperative periods: between postoperative days 10 and 12 and, between postoperative days 18 and 21.Results The age range was 31 to 55 years (38.5±9.5 years) in group A and 25 to 58 years (37.8±9.1 years) in group B, while the mean BMI was 31.4 to 39.9 kg/m2 (32.6 kg/m2) in group A and 32.7 to 37.4 kg/m2 (31.5 kg/m2) in group B. In group A, the patients had a complication rate of 10% in group A versus 43% in group B (P<0.05). The incidence of seroma formation was 3% in the fibrin glue group but 37% in the lipoabdominoplasty-alone group (P<0.05).Conclusions Lipoabdominoplasty with the use of autologous fibrin sealant is a very effective method that significantly reduces the rate of postoperative seroma.
Keywords: Seroma prevention; Lipoabdominoplasty; Autologous fibrin sealant; Fibrin tissue adhesive; Obesity